Effects of galacto-oligosaccharide prebiotics in blood profile of severely acute malnourished children - Rehman, Habib-Ur-; Nasir, Muhammad; Abdul Jabbar, Makhdoom; Ayaz, Muhammad; Ali, Muhammad Asif; Imran, Muhammad; Gondal, Tanweer Aslam; Tufail, Tabussam; Aslam, Farhan; Lal, Sham; Rind, Nadir Ali; Salehi, Bahare; et al. (Cellular and Molecular Biology, 2020)
This study assessed the effects of galacto-oligosaccharides (Oligomate) on hematocrit, serum enzymes, total bilirubin levels, and serum electrolytes in controls and severely malnourished infants, with emphasis on gastrointestinal symptoms. Oligomate doses and phases did not affect stools frequency per day, indicating that prebiotic effect on stool may be due to the prebiotic type. The number of vomits per day during phases 2 and 3 were significantly reduced (p<0.05) in response to prebiotics, despite the prebiotic dose effect was not significant (p>0.05). Moreover, prebiotics administration during phases 2 and 3 markedly improved hemoglobin levels (p<0.05), but not the dose. Similarly, hematocrit levels and white blood cells were significantly improved during the last 2 phases, but dose have no effects on blood hematocrit levels. Erythrocyte sedimentation rate significantly decreased (p<0.05) in phases 2 and 3 compared to phase 1. No dose-related effect was stated on erythrocytes sedimentation rate. Regarding the serum enzymes, SGPT significantly decreased (p<0.05) in phases 2 and 3 compared to phase 1, whereas SGOT significantly decreased only in phase 3. Total bilirubin levels increased significantly (p<0.05) in phase 3 when compared to phases 1 or 2. Prebiotics significantly decreased (p<0.05) sodium levels in the treated group, while potassium levels did not change in all groups, excepting during phase 2, where it increased significantly. Thus, our results confirm the hypothesis that prebiotic supplementation improves blood parameters and health status, consequently decreasing the infection risk and number of vomit per day in infants.